Synthetic Reality. AI, the Metaverse, and the Ethics of a New Digital Humanism - Marsili, M. (2026)
Synthetic Reality explores how artificial intelligence is reshaping the collective mind, society, and the law. Marco Marsili examines the ethical and political transformation triggered by algorithmic power, and argues for a new form of digital humanism grounded in responsibility, transparency, and global cooperation. Bridging philosophy, science, and institutions, the book invites readers to move beyond fear of the algorithm and to build a future in which AI becomes an instrument of freedom rather than domination—restoring to humanity the moral measure of its own power.